THE INFLUENCE OF FIRM FINANCIAL PERFORMANCE ON TAX AVOIDANCE: A META-ANALYSIS STUDY - Chika Sri Mulyati; Carmel Meiden; Yosef Dema (Bajang Institute, 2025)
This research integrates findings from multiple studies obtained through the Publish or Perish (PoP) software and Google Scholar to examine the influence of profitability, leverage, company size, capital intensity, and sales growth on tax avoidance. Previous studies have produced both consistent and inconsistent results regarding the relationship between these variables and tax avoidance, with varying levels of statistical significance. Using purposive sampling, 52 relevant research articles were selected. A meta-analysis technique was employed to synthesize these findings and draw conclusions about the impact of these variables on tax avoidance. The results of the meta-analysis reveal significant relationships between profitability, leverage, company size, capital intensity, and sales growth, with varying degrees of impact on tax avoidance across different studies